Designing and Evaluating a Virtual Patient Simulation—The Journey from Uniprofessional to Interprofessional Learning - Nataly Martini; Kate Farmer; Shambhavi Patil; Gauis Tan; Cindy Wang; Lucy Wong; Craig S. Webster (Information, 2019)
“Ready to Practice?”(R2P) is a virtual patient simulation designed for undergraduate medical and pharmacy students. After initial prototyping, R2P developed into a screen-based virtual patient (VP) simulation with an intuitive interface using photorealistic images of people and places with speech bubbles and decision menus. We describe the design of the VP, findings from student experiences with the software, and the potential of VPs for interprofessional learning. We used a mixed methods study to assess students’ perceptions of the VP as a learning tool. Qualitative data were gathered using semi-structured interviews and observations, and quantitative data through the Readiness for Interprofessional Learning Scale (RIPLS) and an evaluation questionnaire. Overall, participants showed significantly improved RIPLS scores after participation in the simulation (78.78 to 82.25, p < 0.0001), including in the Positive Professional Identify domain (p < 0.001). Students also showed significant improvement in RIPLS scores in the Teamwork and Collaboration domain when pharmacy and medical students were working together in interprofessional pairs (40.75 to 43.00, p < 0.006) but not when working alone (n.s.). Five themes emerged from interviews where participants identified specific interprofessional insights into each other’s roles and skills. Students found the VP engaging and valuable for their learning and their understanding of teamwork.